Fatores críticos de sucesso no mercado bancário brasileiro de comércio exterior: um estudo de caso do Banco Santander Banespa através da estratégia ' Visão baseada em recursos' - Rubega, Teresa Cristina Ferreira (2007)
This dissertation is an exploratory study aiming to identify and analyze key success factors for a bank dealing in the foreign trade market in Brazil through individual interviews and internet based survey with customers and employees of Banco Santander Banespa. The theoretical fundamentals used in this study are based on Operations and Services Management, Marketing of Services and Strategy, which were used to define possible resources and capabilities that could become sources of competitive advantage. After this first stage based on the theory, it follows another stage of field research divided into two steps. The first step was based on interviews with a small number of customers and employees of Banco Santander Banespa located in São Paulo, Rio de Janeiro and Curitiba. The second step was based on a survey with middle-market companies’ customers of Banco Santander Banespa located in several Brazilian states. During the individual interviews a new probable source of competitive advantage was observed, 'Presence of the bank in other countries', and it was included to be investigated through the internet based survey during the second step of the field research. The results obtained were then analyzed in the framework of the VRIO model from the Resource-based View – RBV strategy. The final result pointed as key success factors for banks dealing in the Brazilian Foreign Trade market: flexibility and agility to customize services and products according to the needs of the customer; credit limit approved; price; flexibility, cordiality, technical skills and agility of managers; quality when delivering services and products; technology. Such resources analyzed through the VRIO model suggested that Banco Santander Banespa is currently in a situation of competitive parity in the Brazilian Foreign Trade market.